2012
DOI: 10.1094/pdis-04-11-0297
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Glyphosate on Fusarium Head Blight in Wheat and Barley Under Different Soil Tillages

Abstract: Bérubé, M.-E., Vanasse, A., Rioux, S., Bourget, N., Dion, Y., and Tremblay, G. 2012. Effect of glyphosate on Fusarium head blight in wheat and barley under different soil tillages. Plant Dis. 96:338-344.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Although largely debated [275], the activity of glyphosate weed control in predisposing plants to Fusarium disease by impairing plant defenses has been demonstrated [276] in both wheat and maize [277,278]. However, other studies reported that glyphosate had no significant effect on the FHB index and DON content in wheat and barley [279].…”
Section: Fusarium Disease and Toxins Managementmentioning
confidence: 99%
“…Although largely debated [275], the activity of glyphosate weed control in predisposing plants to Fusarium disease by impairing plant defenses has been demonstrated [276] in both wheat and maize [277,278]. However, other studies reported that glyphosate had no significant effect on the FHB index and DON content in wheat and barley [279].…”
Section: Fusarium Disease and Toxins Managementmentioning
confidence: 99%
“…GR soybeans are a rotation crop with cereals, and recent reports have suggested that glyphosate treatment of soybeans increases the occurrence of Fusarium head blight of wheat and barley. 206 , 207 Because of these observations, Bérubé et al 208 tested the effects of tillage and glyphosate treatment of GR soybean on Fusarium head blight development in a subsequent planting of wheat and barley. There was no measurable effect of treating GR soybeans with glyphosate on development of head blight and accumulation of mycotoxins in barley or wheat.…”
Section: Effects Of Glyphosate On Plant Disease In Glyphosate-resistamentioning
confidence: 99%
“…In minimum-till wheat fields in Canada, the FHB index was higher in fields previously treated with glyphosate (Fernandez et al, 2009a). In another study (Bérubé et al, 2012), glyphosate applied to a soybean crop during the year preceding the wheat crop did not have any effect on the FHB index or DON content. Ryegrass is a widespread weed in wheat-growing regions of Brazil, and glyphosate-resistant ryegrass is common in areas where glyphosate has been applied to agriculturally important crops (Machado et al, 2015).…”
Section: Agricultural Practicesmentioning
confidence: 81%